2018
DOI: 10.1001/jama.2018.1896
|View full text |Cite
|
Sign up to set email alerts
|

Association of Placebo, Indomethacin, Ibuprofen, and Acetaminophen With Closure of Hemodynamically Significant Patent Ductus Arteriosus in Preterm Infants

Abstract: PROSPERO Identifier: CRD42015015797.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
244
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(262 citation statements)
references
References 103 publications
10
244
6
2
Order By: Relevance
“…Paracetamol can also promote successful ductal closure perhaps with fewer renal side effects than ibuprofen [179]. Meta-analyses of all available studies suggest high-dose oral ibuprofen gives better PDA closure rates than intravenous ibuprofen or indomethacin, although no particular regimen compared with placebo influenced any important long-term outcome [180]. Routine indomethacin or ibuprofen treatment of all infants to promote PDA closure is not considered good practice [181].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…Paracetamol can also promote successful ductal closure perhaps with fewer renal side effects than ibuprofen [179]. Meta-analyses of all available studies suggest high-dose oral ibuprofen gives better PDA closure rates than intravenous ibuprofen or indomethacin, although no particular regimen compared with placebo influenced any important long-term outcome [180]. Routine indomethacin or ibuprofen treatment of all infants to promote PDA closure is not considered good practice [181].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…The most effective intravenous ibuprofen-dosing regimen determined in meta-analyses by Mitra et al consisted of a 20 mg kg −1 first dose, followed by additional 10 mg kg −1 doses after 24 and 48 h, all with 15 min infusion rates [19]. Simulation of concentration-time profiles of both ibuprofen enantiomers in a typical neonate with PDA at PNA of 24 h and a body weight of 840 g following this dosage regimen, predicted a corresponding (S)-ibuprofen trough concentration at 48 h after ibuprofen start of 43 mg l −1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of developing side effects and toxicity of nonsteroidal anti-inflammatory drugs seems related to peak concentrations. The meta-analyses by Mitra et al reported less side effects with a continuous administration than an intermittent regimen, although the odds ratio for oliguria of 0.07 was not found significant (0.00–1.84) [19]. Gournay et al reported a placebo controlled trial with major side effects of ibuprofen concerning gastrointestinal adverse effects, severe intraventricular hemorrhages caused by thrombocytopathy, necrotizing enterocolitis, and renal dysfunction [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations